AD, Volume 18, n° 1, 1993 - Full Issue - Journal System, (Africa Development, 1993)
Contents The European Single Market in 1992 and its possible Effects mi African Economies Jean K Thisen ................................ 5 Le discours des officiers soudanais sur les peuples du Soudan occidental de 1850 aux années 1900: l'africanisme français à l'époque de l'expansion militaire Mamadou Moustapha Kane ................. 27 Crisis, Structural Adjustment and Creative Survival in Sierra Leone A B Zack Williams ............................. 53 La répartition des moyens d'incitation à la production entre cultures d'exportation et cultures vivrières en Côte d'Ivoire René Kouassi ............................. 67 Transition Planning in Nigeria: A Critique of the Military Civil Transiting Variant Kunie Amuwo .......................... 87 Book Reviews Gendering African History Tiyambe Zeleza ........................... 99 Steven Feierman, Peasant Intellectuals: Anthropology and History in Tanzania by Steven Feierman, University of Winconsin Press, Madison, 1990, pp.340 Tiyambe Zeleza ..............................118 Patrick Obeng-Fosu, Industrial Relations in Ghana: The Law and Practice , The Ghana Universities Press, Accra, Ghana, 1991, pp.152 Kwamina Panford ........................... 121 Index of Africa Development Vol. XVII, 1992 .........................125